Exploring Oedipus Complex and Hyperactivity - Simbolon, Sangapta; Aris, Qori Islami; Hutahaean, Sorta (Pioneer: Journal of Language and Literature, 2023)
This study aims to analyze the Oedipus complex and the hyperactivity symptoms displayed by the protagonist in the movie 'Mommy'. The research problem is that there has been limited psychological analysis of the potential presence of the Oedipus complex and hyperactivity disorder in fictional characters in films. This gap in research warrants a thorough examination of the protagonist in 'Mommy' to gain deeper insight into the depicted psychological intricacies. Qualitative methodology is used, applying Freud's psychoanalytic theory and Russell Barkley's ADHD theory to analyze dialogues and scene depictions from the film. By systematically identifying and categorizing data pertinent to Oedipus complex and hyperactivity symptoms, conclusions are drawn from the findings. The film's protagonist displays symptoms of Oedipus complex, such as seeking excessive attention from their mother, feeling jealousy towards their mother's romantic partner, engaging in inappropriate physical contact, showing anxiety about maternal separation, and developing affection for an older maternal acquaintance. Furthermore, hyperactivity symptoms manifest with excessive speech, heightened motor activity, and intentional agitation of others. This analysis indicates that the film's main character displays signs of the Oedipus complex and hyperactivity disorder. This thorough examination fills the research gap and allows for a more profound comprehension of the psychological intricacies portrayed in the protagonist.